qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$y = 3 x + 4$
$y = - 6 + 2 x$
$x$Intercept
$\left ( - \dfrac { 4 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , 4 \right )$
$x$Intercept
$\left ( 3 , 0 \right )$
$y$Intercept
$\left ( 0 , - 6 \right )$
$3x+4 = -6+2x$
$x = - 10$
$ $ Solve a solution to $ x$
$3 x + 4 = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x }$
$ $ Organize the expression $ $
$3 x + 4 = \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 6 }$
$3 x + 4 = \color{#FF6800}{ 2 } \color{#FF6800}{ x } - 6$
$ $ Move the variable to the left-hand side and change the symbol $ $
$3 x + 4 \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = - 6$
$3 x \color{#FF6800}{ + } \color{#FF6800}{ 4 } - 2 x = - 6$
$ $ Move the constant to the right side and change the sign $ $
$3 x - 2 x = - 6 \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ x } = - 6 - 4$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = - 6 - 4$
$x = \color{#FF6800}{ - } \color{#FF6800}{ 6 } \color{#FF6800}{ - } \color{#FF6800}{ 4 }$
$ $ Find the sum of the negative numbers $ $
$x = \color{#FF6800}{ - } \color{#FF6800}{ 10 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo